Aliphatic hydrocarbon profiles in sediments of the Forcados River, Niger Delta, Nigeria. Issue 2 (2nd April 2016) - Iwegbue, Chukwujindu M. A.; Aganbi, Eferhire; Obi, Grace; Osakwe, Stephen A.; Eguvbe, Peter M.; Ogala, Jude E.; Martincigh, Bice S.
ABSTRACT: Spatial changes in the concentrations and compositional patterns of aliphatic hydrocarbons in sediments of the Forcados River in the Niger Delta, Nigeria, were studied. The concentrations and identities of the aliphatic hydrocarbons were determined by means of gas chromatography with flame ionization detection (GC/FID). The concentrations of aliphatic hydrocarbons in the Forcados River sediments ranged from 16.2 to 603.3 µg/kg, which were below the UNEP (United Nations Environment Programme) recommended limit of 10, 000 µg/kg. The carbon preference index (CPI) and pristane/phytane ratios indicated that the major source of hydrocarbon pollution in the sediments was of petrogenic origin. The average carbon chain length (ACL) was used to identify the chemical environment. The ACL values were constant at 28 in most of the sampling stations, except for the sampling stations of Yobebe (27.41), Bomadi (26.24), and Abare (27.12), where they were lower due to petroleum contamination in the study area. The ratio of hentriacontane to nonadecane, C31 /C19, indicated that n -alkanes were generated from terrestrial biogenic origins and were transported to the Forcados River by anthropogenic means.